1978
DOI: 10.1111/j.1399-0004.1978.tb02145.x
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominantly inherited adductor laryngeal paralysis ‐ a new syndrome with a suggestion of linkage to HLA

Abstract: A family is reported with autosomal dominantly inherited congenital bilateral adductor paralysis of the larynx. This disorder has apparently not been described previously. A search for linkage in this family with the loci for 19 other genetic markers showed a suggestion of linkage with HLA and GLO, and accordingly a suggestion that the locus for this disorder may be assigned to chromosome 6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Often neonatal stridor and swallowing difficulties are the first manifestations. Linkage of a gene for congenital bilateral adductor paralysis to chromosome 6q16 has been suggested [Mace et al, 1978;Manaligod et al, 2001]. Schinzel et al [1990] reported laryngeal paralysis and intellectual disability in a brother and two sisters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often neonatal stridor and swallowing difficulties are the first manifestations. Linkage of a gene for congenital bilateral adductor paralysis to chromosome 6q16 has been suggested [Mace et al, 1978;Manaligod et al, 2001]. Schinzel et al [1990] reported laryngeal paralysis and intellectual disability in a brother and two sisters.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital aphonia, either isolated or as part of a syndrome, is infrequent. Congenital vocal cord paralysis is the main cause for aphonia and is usually transmitted in an autosomal dominant way [Gacek, 1976;Mace et al, 1978;Morelli et al, 1980;Brunner and Herrmann, 1982;Grundfast and Milmoe, 1982;Cunningham et al, 1985;Tarin et al, 2005]. Often neonatal stridor and swallowing difficulties are the first manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have associated the autosomal dominant form of bilateral VCP with a locus on chromosome 6. In 1978, Mace et al 6 proposed linkage of familial laryngeal adductor paralysis to human leukocyte antigen (HLA) on chromosome 6p21. In 2001, Manaligod et al 7 discovered an allele on chromosome 6q16, which occurred with higher incidence in affected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Patients usually present with bilateral vocal fold paralysis and mental retardation. Autosomal dominant mode of inheritance has also been reported [3][4][5]. Other syndromic associations may be Down's syndrome, Moebius syndrome, congenital myasthenic syndrome, 22q deletion syndrome and Goldenhar syndrome [6].…”
Section: Geneticmentioning
confidence: 99%